2022
DOI: 10.1186/s13018-022-03224-z
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 regulates inflammation and osteogenic differentiation of ankylosing spondylitis fibroblasts through the Wnt-Smad signaling pathway

Abstract: Ankylosing spondylitis (AS) is a refractory autoimmune disease, whose typical pathology is the development of inflammation to ossification and ankylosis. Histone deacetylase 1 (HDAC1) is considered to be a key factor involved in inflammatory gene transduction, but its role in AS remains unclear. The purpose of this study was to explore the role and possible mechanism of HDAC1 in AS based on the Wnt-Smad pathway. Fibroblasts were isolated from hip synovial tissues of AS patients, adeno-associated virus (AAV) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…63 HDAC1 significantly increased the expression of Wnt and β‐catenin in fibroblasts from patients with ankylosing spondylitis. 64 HDAC1, as a deacetylase, in addition to regulating histone deacetylation modification, can also deacetylate other proteins, such as p53. HDAC1 reduces p53 acetylation, which results in instability and degradation of p53.…”
Section: Discussionmentioning
confidence: 99%
“…63 HDAC1 significantly increased the expression of Wnt and β‐catenin in fibroblasts from patients with ankylosing spondylitis. 64 HDAC1, as a deacetylase, in addition to regulating histone deacetylation modification, can also deacetylate other proteins, such as p53. HDAC1 reduces p53 acetylation, which results in instability and degradation of p53.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increasing expression of Wnt signaling inhibitors Dickkopf-1 (Dkk1) caused a synapse dysfunction raised by amyloid deposition. Numerous evidences had indicated that increased HDAC1 expression activated the Wnt pathway [ 32 , 33 ]. This is in line with our results that HDAC1 and HDAC8 participated in the Wnt pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HDAC1 promoted AS fibroblast proliferation, inflammatory response, and osteogenic differentiation via the Wnt-Smad pathway. 12 More than 3-fold increase of HDAC3 mRNA and protein expression were showed in PBMCs from AS patients compared to Healthy controls. Conversely, miRNA-130a expression was significantly lower in PBMCs from AS patients compared with Healthy controls.…”
Section: Histone Deacetylase and Ankylosing Spondylitismentioning
confidence: 95%